UMP Alumni shared joy of happiness with orphans and the asnaf in shopping for the Eid Mubarak - UMP, PNC (2019)
Their faces lit with joy and happiness upon having the chance to choose their own clothes for the coming Aidilfitri celebration. They were 110 children aged between five and 17 who were orphans and from the asnaf group who were brought to shop at the Pasar Raya Hari-Hari under the ‘Ziarah Prihatin Aidilfitri Projek Baju Raya.’